FIKSE OG TRIKSE, ORDNE OG MIKSE! Etnografisk Kongosamling i tre epoker - Wæhle, Esben (Tidsskriftet Antropologi, 2001)
While doing fieldwork in the Democratic Republic Congo (1982-83) the author assembled a collection of objects from the Efe (Mbuti Pygmy) and neighbouring Lese Dese cultivators of the rain forest. This collection was to contribute to the permanent African exhibition of the Ethnographic Museum of the University of Oslo, Norway. Secondly, it was directed primarily at objects which reflected the daily life of the inhabitants of the area so as to contrast to the collections of weapons, religious objects and emblems of power made by Norwegians in the epoch of the Congo Freestate and the early Belgian Congo (1885-1918). If given the chance to collect in this region again, the author would delve into the fascinating and humorous strategies applied by the bricoleurs of the large cities of the Congo. The two existent and the hypothetical collection may not be so different after all. Seen in a historic perspective, all collections attest to material and social strategies for survival and to strategies for making life beautiful and pleasant. Congolese producers have had various sources of inspiration and broad frames of reference for their invention and production of material culture.